Pengaruh Brand Ambassador Terhadap Brand Awareness Aplikasi Ajaib di Media Sosial Instagram - Putra, Aditya Eka; Fianto, Latif; Chun, Nasya Xaverie Liem Wie (Unitri Press, 2024)
The phenomenon of the Korean Wave in Indonesia has led to various Indonesian companies to make South Korean artists as their brand ambassadors. One of these companies is PT Ajaib Group, which has chosen Lisa Blackpink as its brand ambassador. This research aims to analyze the influence of using Lisa Blackpink in marketing content towards Ajaib Application’s brand awareness on @Reaction_Blackpink’s Instagram followers. This study is a quantitative research with an associative approach. The sampling technique used is non-probability sampling, specifically purposive sampling. This study collected data by distributing an online questionnaire to 158 respondents who are fans of Lisa Blackpink, are aware of the Ajaib application, and know that Lisa Blackpink is the brand ambassador of Ajaib Application. The research analysis method SEM-PLS using SmartPLS. In this study, it is found that there is a positive and significant influence of marketing communication content on Instagram using Lisa Blackpink towards Ajaib Application’s brand awareness among the Instagram followers of @Reaction_Blackpink. The magnitude of the influence of marketing communication content on Instagram using Lisa Blackpink towards Ajaib Application’s brand awareness among the Instagram followers of @Reaction_Blackpink is 0.543. Abstrak Fenomena Korean Wave di Indonesia membuat berbagai perusahaan Indonesia menjadikan artis Korea Selatan sebagai brand ambassador perusahaannya, salah satunya adalah PT Ajaib Group yang menjadikan Lisa Blackpink seagai brand ambassador. Penelitian ini bertujuan untuk menganalisis pengaruh dan seberapa besar pengaruh penggunaan Lisa Blackpink dalam konten pemasaran terhadap brand awareness Aplikasi Ajaib pada followers Instagram @Reaction_Blackpink. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan asosiatif. Teknik penarikan sampel yaitu non-probability sampling, purposive sampling. Penelitian ini mengumpulkan data dengan menyebarkan kuesioner secara online kepada 158 responden yang merupakan penggemar Lisa Blackpink, mengetahui aplikasi Ajaib, dan mengetahui bahwa Lisa Blackpink merupakan brand ambassador dari aplikasi Ajaib. Metode analisis penelitian ini adalah SEM-PLS menggunakan SmartPLS. Penelitian mendapatkan hasil bahwa terdapat pengaruh yang positif dan signifikan antara konten komunikasi pemasaran pada Instagram menggunakan Lisa Blackpink terhadap brand awareness Aplikasi Ajaib pada pengikut Instagram @Reaction_Blackpink. Besar pengaruh konten komunikasi pemasaran pada Instagram menggunakan Lisa Blackpink terhadap brand awareness Aplikasi Ajaib pada pengikut Instagram @Reaction_Blackpink adalah sebesar 0.543.